The effectiveness of I-Lab v2 as a teaching tool for online distance learning / Nur Zaidani Wati Mohd Darwis ... [et al.] - Mohd Darwis, Nur Zaidani Wati; Ab Rahim, Noor Raifana; Noh, Narita; Asfar, Juwita (2021)
Due to COVID-19 outbreaks in Malaysia adapting a new norm for teaching and learning is required. UiTM has shifted the teaching and learning from traditional method to Open Distance Learning (ODL) which required sudden changes towards the lecture. All teaching and learning sessions should be conducted online but the concern arises on laboratory courses. Most of the Engineering Programmes in Malaysia are still practicing the traditional method for laboratory courses in delivering process, preparing the laboratory report, and submitting the report. Therefore, i-LAB v2 is introduced for the Water Engineering Laboratory subject in ensuring the CO and PO are achievable and to merge with ODL. i-LAB v2 consists of an excel template that provides all the information regarding the course which is Water Engineering Laboratory. The information includes the laboratory manual, apparatus needed for the experiment, video of the laboratory procedures and a section for the students to prepare their laboratory report. A pilot study on the application of i-LAB v2 was conducted among 29 semester five students. They were given a set of survey to get feedback regarding the effectiveness of this template to be used as a teaching tool for laboratory courses. From the survey given, 44.82% of the students agreed to use i-LAB v2 for preparing laboratory report, while 44.83% of the students were neutral and 10.35% of the students did not agree to use this system. As seen from the survey only 10.35% of the students preferred using the traditional laboratory method for laboratory report preparation and submission due to the template required a big storage that makes it difficult to download on handphone and unable to view the video procedure of the laboratory. Therefore, based on feedbacks received from the survey, i-LAB v2 will continue to be used in this subject. Improvements will be made based on the respondents' feedbacks.